Efficacy in the treatment of depressive disorders - Aquino, Taysa Leite de; Liborio, Jaiany Rodrigues; Bezerra, Ana Luiza Menezes Santana; Cavalcante, Giovana Macêdo Egídio; Duarte, Dara Fernanda Brito; Martin, Ana Luíza de Aguiar Rocha; Paula, Juliane dos Anjos de; Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
IntroductionDepression, being the most disabling disease in the world and presenting high morbidity and mortality, requires an effective treatment to ensure the maintenance of the patients' quality of life. About a third of patients do not respond adequately to antidepressant treatment. New pharmacological therapies are being approached in order to reduce the unfavorable outcomes resulting from this pathology.ObjectiveTo develop a systematic review of the literature on the new possibilities of pharmacological treatments for depression in the last four years.MethodA systematic review was carried out following the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). We have included studies on the effectiveness of new pharmacological therapies in patients with major depressive disorder and treatment-resistant depression.ResultsIn the treatment of the major depressive disorder (MDD), the use of brexpiprazole 1 mg/day in addition to the usual antidepressant treatment (ADT) resulted in significant improvement in the main symptoms. Already referring to treatments for treatment-resistant depression (TRD): nasal esketamine proved beneficial in the short term, intravenous (IV) ketamine also appears as an effective therapy.ConclusionThe use of brexpiprazole 1 mg/day associated with an antidepressant, and the use of lactobacilli represent a new option for those with MDD. In addition, both ketamine, riluzole, and cariprazine appear as new hopes for those who have not yet achieved remission of the depressive disorder with the use of more than two antidepressants